“A Deus pela sciencia; à sciencia por Deus”: os discursos religiosos e científicos do Colégio Diocesano Pio X - Paraíba (1910 - 1954) - Santos, Alexandro dos (2020)
This doctoral dissertation, located in the field of History of Education, analyzes the religious and scientific discourses elaborated by the board of the educational institution Colégio Diocesano Pio X, that supported the words and do science to lead as hygienic, practical and civic cultures in order to promote a school culture in the period from 1910 to 1954 generating, in turn, a school sensitivity towards a strong, healthy and healthy student body. To this end, I problematized the medical, religious, civic, patriotic, militaristic, and pedagogical discourses publicized on newspapers, journals, and yearbooks edited in Paraíba from 1910 to 1954, namely: A União, A Imprensa, Revista do Ensino da Paraíba, Atualidades Pedagógicas, Revista do Colégio Diocesano Pio X, Anuário Eclesiástico da Paraíba, and the pastoral letters written by Dom Adauto Aurélio de Miranda Henriques. As for the theoretical and methodological frameworks, I drew on Michel Foucault’s work on disciplinary power, biopower, and discourse to reflect upon the construction of the religious and scientific project of this educational institution with a view to investigating the practices of hygiene, physical and civic culture intended for pupils. Accordingly, I engaged in dialogue with Dominique Juliá and Antônio Vinão Frago on school culture, and with Sandra Jatahy Pesavento on the History of Sensitivities. In addition to these, I also drew on the field of History of Health, Education, and Body in order to shed light on the areas of research under study. Results demonstrated that the creation of the Colégio Diocesano Pio X was part of a broader and bolder project of “social reconstruction” of part of the state population through education, enacted by the first bishop of the state of Paraíba, Dom Adauto. Thus, it showed to be in line with contemporary discourses that, by that time, defended the Romanization of society, stressing that the teaching of hygiene, physical and civic education was responsible for materializing an educational project that acted upon the body of the youth to have this body modeled, disciplined, trained, medicalized, and taught.